IMPROVING THE QUALITY OF TRAINING OF EDUCATION MANAGERS - Makhmudova, Gulnora (MMIT Proceedings, 2023)
Modern Uzbek society is going through a process during which qualitatively new principles of the organization of pedagogical activity are being formed. In these conditions, the issues of training education managers, their professional competence, initiative, flexibility, ability to adapt to the educational process come to the fore. All these issues can be solved only on the basis of the functioning of an effective education system, in which the organization and conduct of students' training practices plays a key role.